2001
DOI: 10.1200/jco.2001.19.17.3712
|View full text |Cite
|
Sign up to set email alerts
|

Who Gets Adjuvant Treatment for Stage II and III Rectal Cancer? Insight From Surveillance, Epidemiology, and End Results–Medicare

Abstract: Because pelvic recurrences are a substantial cause of morbidity, further efforts are needed to ensure that elderly patients have the opportunity to make informed decisions regarding adjuvant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
84
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(100 citation statements)
references
References 33 publications
11
84
0
5
Order By: Relevance
“…11 In a study of California Cancer Registry data including 1,956 patients, Ayanian et al 12 found that patients age 85 years or older were significantly less likely than younger patients to receive adjuvant radiotherapy for rectal cancers. Schrag et al 13 reported similar results in 1,670 patients with stage II and III rectal cancer identified through the Surveillance, Epidemiology, and End-Results-Medicare linked database. In this study, patients age 85 years or older were significantly less likely to receive radiotherapy or chemoradiotherapy, even after adjusting for degree of comorbidity.…”
Section: Discussionsupporting
confidence: 59%
“…11 In a study of California Cancer Registry data including 1,956 patients, Ayanian et al 12 found that patients age 85 years or older were significantly less likely than younger patients to receive adjuvant radiotherapy for rectal cancers. Schrag et al 13 reported similar results in 1,670 patients with stage II and III rectal cancer identified through the Surveillance, Epidemiology, and End-Results-Medicare linked database. In this study, patients age 85 years or older were significantly less likely to receive radiotherapy or chemoradiotherapy, even after adjusting for degree of comorbidity.…”
Section: Discussionsupporting
confidence: 59%
“…The need for aggressive social policy is only highlighted further here. Differences in receipt of treatment have been reported in many prior studies (38)(39)(40)(41)(42)(43)(44). A major finding of ours was that African-Americans received surgery less often than in the other groups.…”
Section: Discussionsupporting
confidence: 58%
“…Prior research has shown that not only do treatment rates decline dramatically with increasing age [51], but older age is associated with delayed chemotherapy initiation [52] and lower rates of chemotherapy completion [53]. These age disparities in treatment patterns are associated with higher mortality [52,53] and In addition, the SEER-Medicare database does not provide data on performance status or lifestyle factors, such as smoking.…”
Section: Discussionmentioning
confidence: 99%